Evaluation of the Possibility of Using Industry Mineral Waste in Agriculture, Russia - Zolotova, Ekaterina (International Journal of Bio-resource and Stress Management, 2019)
The main conditions for the application of waste are the excess concentration of elements that the soil needs, and environmental safety. The protective properties of soils are important to consider when applying unconventional fertilizers. The possibility of using mining waste, coal enrichment and thermoelectric stations wastes, chemical wastes, ferrous and non-ferrous metallurgy wastes for growing plants was examined. Studies on the use of agronomic ores to improve soil fertility started in Russia a long time ago. Currently, scientists are conducting research on nanosuspensions of agrominerals: brown coal, glauconite, sapropel and phosphate, and its application in particular for pre-sowing treatment of seed. Experience of application in agriculture of combustible shale ash and brown coal, sulfate wastes has been accumulated. Phosphogypsum can be used as a chemical ameliorant, as it contains up to 94% CaSO4, and as a calcium-phosphorus-sulfur fertilizer. The use of waste from ferrous and non-ferrous metallurgy in agriculture is the most difficult, but of particular interest. We focus on the possibility of using waste from the secondary processing of copper smelting slag for the cultivation of some agricultural plants. The addition of 5% waste from the secondary processing of dump copper-smelting slag to the soil had a stimulating effect on the investigated plants: germination, development and growth increased. Research is important for understanding the transformation of biogeochemical cycles in the conditions of technogenesis and ensuring sustainable development.